Європейські юнацькі олімпійські фестивалі: історія проведення та аналіз результатів виступів українських атлетів - Веселова, Вікторія В`ячеславівна; Малинський, Ігор Йосипович; Тимощенко, Павло Юрійович (Український державний університет імені Михайла Драгоманова, 2026)
У науковій публікації проаналізовано науково-методичну літературу, електронні ресурси щодо історії створення та організації Європейських юнацьких олімпійських фестивалів, географію міст-організаторів ЄЮОФ та результати виступів юних українських спортсменів. Зроблено теоретичний аналіз і узагальнено дані щодо організації проведення Європейських юнацьких олімпійських фестивалів, історію створення, вікові категорії учасників, види спорту, які входили до програми мультиспортивних заходів та проаналізовано результати виступів юних олімпійців - членів збірної команди, медального заліку та зайнятих місць у неофіційному командному заліку. Мета публікації - часткове висвітлення організації та проведення ЄЮОФ, акцентування уваги на важливості реалізації таких заходів на Європейському континенті, участі молоді до 18 років у змаганнях, що сприяє подальшим їх виступам на чемпіонатах світу, Європи, Олімпійських та Європейських іграх, продовженні спортивної кар’єри.

In the scientific publication, the authors analyzed scientific and methodological literature and electronic resources concerning the history of the establishment and organization of the European Youth Olympic Festivals. The geography of the EYOF host cities and the performance results of young Ukrainian athletes were also examined. A theoretical analysis was conducted, and the data regarding the organization of the European Youth Olympic Festivals (EYOF) were summarized, including their history of creation, participants’ age categories, and the sports included in the program of these multisport events. In addition, the performance outcomes of young Olympians - members of the national team - were analyzed, as well as the medal standings and the places achieved in the unofficial team rankings. The aim of the publication is to provide a partial overview of the organization and conduct of the European Youth Olympic Festivals, to emphasize the importance of implementing such events on the European continent, and to highlight the participation of youth under the age of 18 in competitions that contribute to their further performances at the World and European Championships, the Olympic and European Games, and to the continuation of their sporting careers.
Keywords: Європейські олімпійські юнацькі фестивалі; історія Олімпійського спорту; дитячий і юнацький спорт; організація та управління у сфері фізичної культури і спорту; European Youth Olympic Festivals; history of Olympic sport; children’s and youth sport; organization and management in the field of physical culture and sport